Endoscopic surgery in Japan: The 12th national survey(2012–2013) by the Japan Society for Endoscopic Surgery. Issue 4 (4th October 2017) - Bandoh, Toshio; Shiraishi, Norio; Yamashita, Yuichi; Terachi, Toshiro; Hashizume, Makoto; Akira, Shigeo; Morikawa, Toshiaki; Kitagawa, Yuko; Yanaga, Katsuhiko; Endo, Shunsuke; Onishi, Kiyoshi; Takiguchi, Shuji; et al.
Abstract: In Japan, the first endoscopic surgery, a laparoscopic cholecystectomy, was performed in 1990. Since then, operative procedures have been standardized, and the safety and usefulness of endoscopic surgery have been evaluated. With the acceptance of endoscopic surgery as less invasive than open surgery, the number of the endoscopic procedures continues to increase in all surgical domains. The Japan Society for Endoscopic Surgery (JSES) has had an important role in the development of endoscopic surgery in Japan. For example, JSES established a technical skills certification system for physicians to train instructors to teach safe endoscopic surgery. Additionally, JSES has performed a national survey every 2 years. In 2013, 178 084 patients underwent endoscopic surgery in all surgical domains, including abdominal, thoracic, mammary and thyroid gland, cardiovascular, obstetrics and gynecology, urologic, orthopedic, and plastic surgery. The development and current status of laparoscopic surgery are reported here based on the results of the most recent questionnaire survey conducted by JSES.